The Equivalents a story of art, female friendship and liberation in the 1960s - Doherty, Maggie (New York : Alfred A. Knopf, 2020)
"An important debut work of narrative nonfiction: the timely, never-before-told story of five brilliant, passionate women who, in the early 1960s, converged at the newly founded Radcliffe Institute for Independent Study, stepping outside the domestic sphere and shaping the course of feminism in ways that still resonate today. In 1960, at the height of an era that expected women to focus solely on raising families, Radcliffe College announced the founding of an Institute for Independent Study, offering fellowships to women with a PhD or "the equivalent" in artistic success. Acclaimed writer and Harvard lecturer Maggie Doherty introduces us to five brilliant friends--poets Anne Sexton and Maxine Kumin, painter Barbara Swan, sculptor Mariana Pineda, and writer Tillie Olsen--who came together at the Institute and would go on to make history. Drawing from their notebooks, letters, lecture recordings, journals, and finished works, Doherty weaves from these women's own voices a moving narrative of friendship, ambition, activism, and art. Beautifully written and urgently told, The Equivalents shows us where we've been--and inspires us to go forward"
Keywords: Radcliffe Institute for Advanced Study / Geschichte 1960-1969; Sexton, Anne; USA / Frauenliteratur / Geschichte 1960-1969